PENINGKATAN HASIL BELAJAR MELALUI MODEL NUMBER HEAD TOGETHER BERBANTUAN MEDIA PERMAINAN ENGKLEK PADA SISWA KELAS VI DI SD NEGERI SARIREJO - Roni Wisnu Wardaniel; Fine Reffiane; Muhammad Prayito (STKIP Subang, 2023)
The study aims to analyze the improvement of learning outcomes of grade VI students of SD Negeri Sarirejo with a total of 25 students. The research method used is classroom action research. The research stage consists of: planning, action, supervision, reflection. Data collection methods of interviews, observations, tests and documentation. Data collection instruments in the form of observations, tests and documentation. Data analysis techniques are qualitative and quantitative descriptive data analysis techniques. The results showed that the learning outcomes of grade VI students of SD Negeri Sarirejo with an increase of 26% from cycles I and II. The results of the First Cycle Analysis showed that 62% of student learning outcomes experienced a significant increase in the second cycle of 88% in the good category. So the use of NHT using crank game media can improve student learning outcomes.